INTEGRATED ASSORTMENT CLUSTERS: A STRATEGIC FRAMEWORK FOR BULLWHIP EFFECT MITIGATION AND INNOVATION ADOPTION IN AGRICULTURAL SUPPLY CHAINS - Gnanakumar, P.Baba (International Journal of Research -GRANTHAALAYAH, 2025)
Agricultural production cannot be controlled. It is difficult to estimate the demand for agricultural commodities because of bullwhip and cobweb effects. In order to raise prices through the control of supplies, farmers must act as a group. The large numbers of farmers and their differing economic circumstances frustrate any attempts to organize and market jointly. This phenomenon leads to the introduction of the integrated assortment cluster (IAC). IACs are introduced as a distinct collaborative model, differentiated from traditional cooperative farming. They involve independent agriculturists orchestrating their diverse production activities to deliver specific product assortments to the market precisely when needed. This study, conducted in South Indian farmers’ markets, examines 21 informal IACs, focusing on their operational strategies to stabilize supply and demand. The research aims to identify how IACs reduce the bullwhip effect, optimize supply chain policies, and manage obsolescence and opportunity costs. Furthermore, it analyzes the adoption of new farming methods within these clusters and the discriminant factors influencing participation and success among small and medium farmers. Findings contribute to understanding effective collective action models for enhancing agricultural market stability and farmer resilience during the period of climate change.